Assessment of indoor thermal condition on traditional vernacular masjid: a case study on masjid kampung laut, Malaysia - Nur Athirah binti Khalit,; Zuraini binti Denan,; Aliyah Nur Zafirah Sanusi,; Norwina Mohd Nawawi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Traditional vernacular architectures in Malaysia include public buildings such as a masjid were designed with the tropical climate in mind and have proven to be an excellent example of providing indoor thermal comfort to the occupants. It is a naturally ventilated building being greatly influenced by the building designs. In traditional vernacular architecture, the roof is the main building enclosure that contributes to the total heat gain. Hence, the research aims to assess the indoor thermal condition of Masjid Kampung Laut, Kelantan, the first traditional vernacular masjid in Malaysia. Data were collected using the method of field measurement to evaluate the indoor comfort level of the masjid, in terms of indoor air temperature, air velocity, and relative humidity. The results demonstrate that the average indoor air temperature is acceptable and Masjid Kampung Laut responded favorably to the local climate. However, it is believed that with an increase of 0.4m/s to 1.2m/s of air movement, will further enhance indoor thermal comfort. Therefore, the findings can guide further thermal comfort prediction studies for other naturally ventilated buildings. Several other potential passive design strategies for roof design are proposed in this study to achieve acceptable indoor thermal comfort conditions for the masjid in Malaysia.